The Role of Members of the North Sumatra DPRD from the Gerindra Faction in Pursuing Community Aspiration - Azizul Hakim Nugraha (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study discusses the role of members of the North Sumatra DPRD from the Gerindra Faction in Pursuing Public Aspirations. In accordance with Law Number 23/2014 concerning Regional Government, the DPRD of North Sumatra, especially the Gerindra Faction. This research was conducted using a qualitative approach. The information studied is information from the Gerindra faction, staff and management of the Gerindra Faction who are members of the North Sumatra DPRD, totaling 5 people. The results showed that the forms of community aspirations were aspirations in the form of oral, individual, demonstration, or work visits. The aspiration was not immediately responded to or resolved, but still through the mechanism following the procedures in the North Sumatra Regional Legislative Institution. The aspirations of the people who are accommodated will be perfected to become a policy, the realization of a policy depends on the executive, on the other hand the legislature only recommends and supervises all performance and policies of the executive body.